Impacts of new school facility construction: An analysis of a state-financed capital subsidy program in Ohio. (August 2017) - Conlin, Michael; Thompson, Paul N.
Highlights: This paper analyzes the Ohio School Facilities Commission (OSFC) Classroom Facilities Assistance Program, which disbursed over $10 billion towards the improvement of local school facilities in 231 school districts between 1997 and 2011. Using an instrumental variables identification strategy based on the yearly rankings and cutoffs used to determine eligibility for this state-financed capital subsidy program, we examine the effect of capital expenditures and increases in the value of the capital stock on student performance and housing prices from 1997 to 2011. In terms of student performance, we find decreases in the percentage of students in the school district that tests proficient in math and reading in the first couple of years after the capital expenditures and increases once the construction of new and renovated buildings is completed. This short-term decline is consistent with the premise that construction projects are disrupting student learning, but over the long-term students appear to benefit from the improved capital stock. We also examine the mechanisms through which these construction projects affect district test scores. Our descriptive analysis indicates that operating expenditures increase after six years of program eligibility, as the capital subsidy may allow districts to redirect general funds from capital to operating expenditures. We also find some evidence that program eligibility is correlated with changes in student body composition – suggesting that perhaps student enrollment decisions are influenced by improvements in building quality. We find negative housing price effects of recent capital expenditures, but positive long-term impacts of these capital investments. This negative short-term effect could be the result of homeowners paying taxes towards funding these projects while the ongoing capital projects provide little immediate benefit. Once construction is complete, however, the positive benefits of the new capital stock are fully realized and the disruption costs of construction are no longer present, leading to positive housing price effects. Abstract: This paper analyzes Ohio's capital subsidy program which distributed over $10B for school construction in 231 school districts between 1997 and 2011. Using an instrumental variables estimation, we find the percentage of students meeting test score proficiency thresholds decrease in math and reading in the first couple years after the capital expenditures and then increase in subsequent years. These results are consistent with short-term disruptions in student learning followed by long-term benefits from the capital expenditures. We also consider mechanisms by which capital expenditures affect achievement and find some evidence that changes in capital expenditures are correlated with changes in operating expenditures, suggesting that some of these effects may be attributable to operating expenditures. We find similar effects of these capital investments on the housing market. While in the short-term these construction projects decrease home prices, the housing market does benefit in the long-term from improvements to the capital stock.